KR-12-a5 Reverses Adverse Effects of Lipopolysaccharides on HBMSC Osteogenic Differentiation by Influencing BMP/Smad and P38 MAPK Signaling Pathways - Li, Hui; Zhang, Shutao; Nie, Bin’en; Long, Teng; Qu, Xinhua; Yue, Bing (Frontiers in Pharmacology, 2019)
KR-12-a5 is an analogue of the antimicrobial peptide KR-12. Both of these two agents can play key effects in the treatment of infections such as osteomyelitis. Our previous work demonstrated that the osteogenic differentiation of human bone marrow mesenchymal stem cells (HBMSCs) can be enhanced by KR-12. The present study investigated if KR-12-a5 could reverse the adverse effects of lipopolysaccharides (LPS) on HBMSC osteogenesis and the involved molecular mechanisms. We observed the proliferation, cell cycle, and apoptosis of HBMSCs in the presence of KR-12-a5 by a cell counting kit-8 assay and flow cytometry. The osteogenic differentiation of HBMSCs was studied by alkaline phosphatase, Alizarin Red staining, and quantitative assays. Osteogenic differentiation marker levels were detected using real-time quantitative PCR analysis, which demonstrated that KR-12-a5 treatment reversed the inhibition of osteogenesis. Western blot analysis indicated that LPS-activated P38 MAPK signaling was inhibited and BMP/Smad pathway was reactivated after KR-12-a5 treatment under induced osteogenic conditions. Furthermore, flow cytometry results demonstrated that KR-12-a5 relieved LPS-induced oxidative stress. Combining the LPS-treated mouse model results, we proved that KR-12-a5 reversed the adverse effects of LPS on HBMSC osteogenic differentiation by influencing the BMP/Smad and P38 MAPK signaling pathways.